Attitudes and beliefs of Tunisian High-School teachers about schizophrenia: The impact of vignette gender. (December 2022) - Fekih-Romdhane, Feten; Smaoui, Olfa; Jahrami, Haitham; Cheour, Majda
Background: Teachers have a crucial active role in provision of mental health services to students and fighting against mental health stigma in schools, hence their attitudes and beliefs toward mental illness should be assessed. Method: We carried-out a cross-sectional study with a non-probabilistic sample of 304 higher secondary school teachers. We used a structured questionnaire in which a vignette describing an individual with schizophrenia was presented, and was followed by a series of stigma-related questions. Results: A substantial proportion of teachers endorsed stressful life events (79.6%) as a cause of schizophrenia, elicited feelings of discomfort (41.4%) and incomprehension (41.1%) with the person displaying symptoms of schizophrenia, and agreed that the person's condition will deteriorate even more (45.4%). Teachers perceived that the person described in the vignette is dependent on others, lacks will, is different from others and is unpredictable in 65.1%, 59.2%, 55.6%, and 49.7% of cases, respectively. In addition, 38.5% and 34.2% of teachers recommended turning to traditional healers and to a Sheikh or an imam of a mosque, respectively. Regarding gender effects, females with schizophrenia were regarded as more likely to be unable to make her own decisions and to be dependent on others than males, and were less likely to be recommended for seeking help from a family physician or to consult a psychiatric hospital than males. Conclusion: In the light of our findings, raising awareness of teachers of the impact of mental health issues on students should be prioritized in high schools in Tunisia.